3D bedroom decoration - Nurazma, Ariffin (2012)
Bedroom is important to everyone where people usually sleep for the night or relax during the day.About one third our live are spent sleeping and most of the time we are sleep, we are sleeping in a bedroom.So,environment in the bedroom will affect people become more relax.This system uses the 3D model to make so that it becomes more interesting to use it. The objectives to develop the applications are:(1)To develop a prototype of bedroom decoration that allows user to decorate their room.(2)To apply 3D modelling technique to the system This system also have made the users task become easier and faster than before.They can view the 3D model in this system.Besides that,this system also provides a great 3D perspective of the bedroom decoration.It makes it possible to create 3D graphic